THE ROLE OF INTERNATIONAL ECONOMIC ACTIVITY OF NON-FARM ENTERPRISES IN RURAL AREAS - Wiśniewska, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2012)
The article analyzes the share of international trade and foreign capital in non-farm companies in rural areas in 2005 and 2010. It enabled verification of the hypothesis on changes, forms and levels of international business. It argues that the internationalisation of the researched companies depends on the size of the company as well as its location. The important determinants influence the process: potential and agglomeration effect. They are responsible for the differentiation of international business activities of companies in agricultural and urbanised areas. The argued phenomena exert negative influence on sustainable development of national economy.